Implementación de metodologías cualitativas para la evaluación visual de Ríos. Estudio de Caso Río Chicamocha Tramo Tibasosa (2022)
The objective of this research is to evaluate the environmental impact presented in the Chicamocha River within the section that circulates through the municipality of Tibasosa (Boyacá) through the use of established methodologies for the visual evaluation of rivers taking three photography points. In addition, the characterization of the study area, physicochemical and microbiological analyzes were carried out, applying the visual evaluation protocol and baseline monitoring charts, surveillance monitoring and the ecological state in which these two are in collaboration with the community, it was identified that the river generates high pollution due to discharges, livestock farms and contaminants derived from agriculture such as fruits, legumes present effects on human health due to indirect consumption